2 - Autoethnography, Reflexivity, and Insider Researcher Dynamics: Reflections on Investigating Violence against Men in Intimate Relationships - Emmanuel Rowlands, (African Sociological Review, 2022)
Autoethnography is a qualitative research method for relating lived-through personal experiences to a range of existing social representations. It is regarded as self-representation in examining and critiquing dominant representations. While the researcher’s subjectivities are restricted within the ethnographic qualitative framework, autoethnography emphasises this foundation as essential to data collection, interpretation, and analysis in the research process. In this paper, I discuss how my lived-through personal experience of abuse influenced how/why I conceptualised, investigated, and represented the lived experiences of several abused male victims of intimate partner violence in Johannesburg, which are typically ignored in gender- based violence literature. The paper comments on tactics used to negotiate ethical dilemmas as part of a conceptual examination of the benefits of reflexivity and insider positionality to reinforce the self-reflective autoenthgrapahy as a valuable qualitative method.